Applying an Intersectionality Approach to Multiple Dimensions of Social Life - Milda Longgeita Pinem (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to identify various research studies on multiple dimensions of social life that employ an intersectionality approach. The approach is a framework that recognizes the multiple dimensions of social identity and how they intersect and influence experiences of discrimination, privilege, and marginalization. Using literature studies from various research databases and employing specific keywords, four dimensions of social life have been identified as dominant themes in research applying the intersectionality approach, namely education, healthcare, politics, and workplace. In the domain of education, the article discusses how an intersectionality approach can help to understand how multiple identities, such as race, gender, and class, intersect to influence educational experiences and outcomes. The article also examines the impact of intersectionality on access to healthcare, highlighting how multiple identities can affect access to care, treatment outcomes, and experiences of discrimination. In politics, the article discusses how an intersectionality approach can help understand marginalized groups' experiences in political processes and systems. The article also examines how intersectionality can influence workplace experiences and opportunities for advancement. The article argues that an intersectionality approach can help to identify and address systemic inequalities and promote greater equality and diversity in multiple dimensions of social life. The article highlights the importance of applying an intersectionality approach in understanding the complex ways social identities intersect and shape experiences of discrimination, privilege, and marginalization.